Ski-Specific Flexibility - Griffin, F.
Target areas: large muscle groups; hips, ankles, shoulders, trunk Objective: improve ski-specific body alignment through muscle stretching and joint flexion improve stability through a range of motion, equalize left-right muscle dominance patterns Duration: 10 - 12 minutes Groundrules: 1.relax into a stretch; no pulling, pushing, bobbing allowed 2.hold every position for between 30 - 60 seconds 3.breathe! Never stop breathing 4.discontinue a stretch if you feel sharp pain, particularly in a joint area Program: the following exercises are meant to be done in sequence. Once athletes have gotten comfortable with the required alignments and movements, they should transition from one position to the next with no more than a few seconds in between. Repeat program from the beginning for a more thorough, deep-muscle stretch is desired. Note: most of your athletes will find many of the positions hard to achieve initially, but after 3 - 5 sessions most will reach a level of flexibility in most positions to allow a more complete range of motion. Mastery of proper alignment and stability over a full range of motion requires regular practice of technique over a period of time not unlike skiing.